Facet‐Oriented Coupling Enables Fast and Sensitive Colloidal Quantum Dot Photodetectors. Issue 33 (10th July 2021) - Biondi, Margherita; Choi, Min‐Jae; Wang, Zhibo; Wei, Mingyang; Lee, Seungjin; Choubisa, Hitarth; Sagar, Laxmi Kishore; Sun, Bin; Baek, Se‐Woong; Chen, Bin; Todorović, Petar; Najarian, Amin Morteza; et al.
Abstract: Charge carrier transport in colloidal quantum dot (CQD) solids is strongly influenced by coupling among CQDs. The shape of as‐synthesized CQDs results in random orientational relationships among facets in CQD solids, and this limits the CQD coupling strength and the resultant performance of optoelectronic devices. Here, colloidal‐phase reconstruction of CQD surfaces, which improves facet alignment in CQD solids, is reported. This strategy enables control over CQD faceting and allows demonstration of enhanced coupling in CQD solids. The approach utilizes post‐synthetic resurfacing and unites surface passivation and colloidal stability with a propensity for dots to couple via (100):(100) facets, enabling increased hole mobility. Experimentally, the CQD solids exhibit a 10× increase in measured hole mobility compared to control CQD solids, and enable photodiodes (PDs) exhibiting 70% external quantum efficiency (vs 45% for control devices) and specific detectivity, D * > 10 12 Jones, each at 1550 nm. The photodetectors feature a 7 ns response time for a 0.01 mm 2 area—the fastest reported for solution‐processed short‐wavelength infrared PDs. Abstract : A strategy to achieve enhanced coupling from colloidal quantum dot (CQD) inks is introduced. By using colloidal atomic layer deposition, the surface of CQDs is reconstructed to facilitate coupling along the (100) facets and increase coupling. This increases the hole mobility by one order of magnitude and enables the fabrication of record‐speed solution‐processed short‐wavelength infrared photodiodes.